Effectiveness of Analgesic Use in Lymphoma Cancer Patients - O'on Sekar Arum (LPPM Universitas dr. Soebandi, 2024)
Background: Lymphoma is an immunological malignancy originating from lymphotic cells that grow uncontrollably and accumulate in the lymph nodes, so it rarely causes a clinical picture as lymphotic. Lymphoma cancer can occur from several factors such as viral infections, family factors, age, gender. Pain is an uncomfortable sensation of sensory and emotional associated with tissue damage. Pain appears at any stage of the disease and can even be the first symptom felt when a malignancy is diagnosed. The purpose of this study was to determine the effectiveness of analgesics use in lymphoma cancer patients. Method: This study design uses cross-sectional which is a type of observational research design. The sample used in this study was 31 patients which is the total of the population.. The independent variable in this study is the use of analgesics, while the dependent variable in this study is the effectiveness of analgesics. Results: The results of this study obtained a pain scale before using the drug of 4.55 and after the use of the drug of 3.77, this study also used an analysis test using a paired t-test with a p-value of 0.00 which means there is a significant difference between before the use of analgesics to after the use of analgesics. Conclusion: The scale of pain before and after the use of analgesics has significant differences, the results of analytical trials in studies before and after drug use also experienced significant differences.